Pulmonary tuberculosis in a patient with the tennis racket sign. A case report - Irene Estefania Delgado Pérez; Marileydis Almaguel García; José Sánchez Prieto (Medisur)
Pulmonary tuberculosis can affect any organ and its clinical manifestations are variable. A case of pulmonary tuberculosis with diagnosis, treatment and follow-up in Primary Health Care is presented. The 52-years-old patient, discharged as a group III adult, at risk of pulmonary tuberculosis, hypertensive and diabetic, was treated at her family doctor's office due to physical discomfort, productive and persistent cough mainly at night, anorexia and asthenia. She had lived for five years with two relatives diagnosed with pulmonary tuberculosis. Radiological examination and microbiological study confirmed the diagnosis. The treatment achieved the improvement, evident from the clinical and radiological point of view; as well as the decrease in the coding in the bacilloscopy. Confirmation of the diagnosis is essential, especially in those patients with risk factors. Chest X-ray and smear microscopy guarantee follow-up. The extended cavitary radiographic image, also known as the tennis racket or arrowhead sign, is rarely seen at diagnosis in the community.